Influência das intervenções assistenciais sobre a continuidade do sono de pacientes em Centro de Terapia Intensiva - Fernanda Luiza Hamze (2012)
Sleep is fundamental for rest, wellbeing, and for the preservation ofhomeostasis and equilibrium of different organ systems of the individual.Patients admitted to the Intensive Care Unit may present alterations in different body systems, among which those related to sleep stand out. Obtaining the best possible quality of sleep is important for the recuperation and health promotion of individuals. Sleep deprivation, changes in sleep-wake cycle and frequent awakenings are common in patients hospitalized in the Intensive Care Unit and have been the object of research in the health area. The aim of this study was to identify interventions care provided by the health team and its influence on sleep continuity of patients admitted to the Intensive Care Unit.This was a descriptive study, with a sample consisting of 12 patients for whom thenursing diagnosis "disturbed sleep pattern" was identified. Data collection was conducted from June to November 2011, using a filming technique for visualization of care interventions performed by the health team during a period of 24 hours. The alterations in sleep patterns were measured by awakenings through the means of actigraphy equipment. We used descriptive statistics for data analysis. There were 529 care interventions identified, grouped into 28 different types of interventions, with an average of 44.1 interventions / patient / day. The most frequent interventions were: measurement of vital signs (109 - 20.6%), assessment of patients (90 - 17.0%), medication administration (84 -15.9%), administration of oral feeding (72 - 13.6%) and blood glucosemeasurement (41 - 7.8%). The distribution of care interventions over the 24 hours did not follow a regular pattern and showed peak occurrences at 10:00 and 22:00 hours. There were 1.8 interventions / hour performed for each patient. In only five patients were there intervals of 120 uninterrupted minutes observed without the performance of an intervention. Among the 529 care interventions performed, 21 (4.0%) caused alterations in patients' sleep, the most common being: medication administration (4 - 19.9%), administration of oral feeding (3 - 14.3%), patient assessments (2 - 9.4%), bath (2 - 9.4%), bloodsampling (2 - 9.4%) and measurement of vital signs (2 - 9.4%). It is concluded that care interventions performed by the health team can disrupt the sleep of patients admitted to the Intensive Care Unit, which points to the need to standardize care, differentiating them according to the severity of each patient with a willingness to diversify their implementation schedules.